LAERNING INTEREST AND CRITICAL THINKING SKILLS THROUGH INTERACTIVE MAP-BASED LEARNING MEDIA IN HISTORY EDUCATION - Hasan Mukhlis; Muhammad Iqbal Birsyada (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to increase students' interest in learning and critical thinking skills through the application of interactive map-based learning media in History lessons in Grade X at SMA Negeri 1 Prambanan Klaten. The background of this study is the low interest of students in learning history and the suboptimal critical thinking skills demonstrated by students during the learning process. This is due to the use of conventional learning methods that tend to be monotonous and do not actively involve students. Therefore, interactive maps are expected to be an alternative solution in creating an engaging and participatory learning environment. This study employs the Classroom Action Research (CAR) method by Kemmis and McTaggart, consisting of two cycles. The research subjects are 35 students in Grade X J. Data collection techniques include observation, questionnaires, interviews, written tests, and documentation. Each cycle consists of four stages: planning, implementation of actions, observation, and reflection. The instruments used aim to measure improvements in students' learning interest and critical thinking skills during the learning process. Based on the research results, it can be concluded that the application of interactive map-based learning media significantly improves students' learning interest and critical thinking skills. There was a gradual increase in students' learning interest, with the average score rising from 58.1 in the pre-cycle to 63.4 in cycle I, and reaching 72.3 in cycle II. The greater increase in cycle II indicates that students became more actively engaged and motivated as the learning process progressed. Similarly, critical thinking skills showed an increase in average scores from 66 in the pre-cycle to 71 in cycle I, and a sharp increase to 84 in cycle II. The drastic increase in the second cycle proves that interactive map-based learning media is effective in increasing students' interest in learning and critical thinking skills in history learning.